The Life of Isaac Ingalls Stevens, Volume 1 (of 2) - Stevens, Hazard, 1842-1918 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Life of Isaac Ingalls Stevens, Volume 1 (of 2)" by Hazard Stevens is a historical account written in the late 19th century. This biography narrates the life and notable achievements of Isaac Ingalls Stevens, a prominent figure in American history, known for his contributions during the Civil War and as a governor of Washington Territory. The text is not only a personal memoir but also serves to inspire future generations with the virtues of patriotism and dedication reflected in Stevens's life. The opening of the book sets the stage for an exploration of Isaac Ingalls Stevens's ancestry and early life, tracing his lineage back to the founding of Andover, Massachusetts, in the 1640s. It introduces Stevens as a delicate child who faced numerous challenges but displayed a strong will and determination to succeed from a young age. The text details his upbringing on a farm, his deep connection to his mother, and his struggle against educational pressures and physical ailments, providing insights into his character formation and the foundational experiences that led to his future endeavors as a soldier and public servant. (This is an automatically generated summary.)
Release date is 2013-08-30
E-text prepared by KD Weeks, Jana Srna, Bryan Ness, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the Google Books Library Project (http://books.google.com)
Keywords: United States -- History -- Civil War, 1861-1865 -- Campaigns; Mexican War, 1846-1848 -- Personal narratives; Northwest, Pacific -- History; Stevens, Isaac Ingalls, 1818-1862; Pacific Coast Indians, Wars with, 1847-1865